2015
DOI: 10.1016/j.drugalcdep.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 7-day continuous d-amphetamine, methylphenidate, and cocaine treatment on choice between methamphetamine and food in male rhesus monkeys

Abstract: Background Methamphetamine addiction is a significant public health problem for which no Food and Drug Administration-approved pharmacotherapies exist. Preclinical drug vs. food choice procedures have been predictive of clinical medication efficacy in the treatment of opioid and cocaine addiction. Whether preclinical choice procedures are predictive of candidate medication effects for other abused drugs, such as methamphetamine, remains unclear. The present study aim was to determine continuous 7-day treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…Consistent with these clinical trial and human laboratory results, a single preclinical study in nonhuman primates also reported that subchronic d ‐amphetamine treatment failed to decrease methamphetamine versus food choice at the group analysis level. However, individual subject analysis revealed methamphetamine choice was decreased in two of the four monkeys . Altogether, this literature does not provide robust support for the utility of monoamine transporter substrates as potential agonist–based substitution pharmacotherapies for methamphetamine use disorder.…”
Section: Evaluation Of Candidate Medications In Preclinical Drug Verssupporting
confidence: 55%
“…Consistent with these clinical trial and human laboratory results, a single preclinical study in nonhuman primates also reported that subchronic d ‐amphetamine treatment failed to decrease methamphetamine versus food choice at the group analysis level. However, individual subject analysis revealed methamphetamine choice was decreased in two of the four monkeys . Altogether, this literature does not provide robust support for the utility of monoamine transporter substrates as potential agonist–based substitution pharmacotherapies for methamphetamine use disorder.…”
Section: Evaluation Of Candidate Medications In Preclinical Drug Verssupporting
confidence: 55%
“…By contrast, an experimental manipulation that produces reinforcement-independent rate-altering effects (e.g., motor impairment) would be expected to decrease rates of behavior and may or may not alter drug choice. An example of this effect is shown (Figure 4) during continuous 7-day treatment with the monoamine uptake inhibitor methylphenidate on methamphetamine versus food choice [15]. Second, as noted above, clinical treatment goals of substance-use disorders include not only decreasing drug-maintained behavior, but also increasing nondrug-maintained behavior [9,11,12,16].…”
Section: Preclinical Drug Choicementioning
confidence: 99%
“…Effects of Continuous Treatment with the Monoamine Uptake Inhibitor (+)-Methylphenidate on Choice between (+)-Methamphetamine and Food in Rhesus Monkeys ( N = 4) [15]. (A,B) Saline and methylphenidate treatment effects on methamphetamine choice dose–effect functions.…”
Section: Figurementioning
confidence: 99%
“…Overall, the present results and the broader scientific literature cited support DAT inhibitors as candidate ‘agonist’ medications for methamphetamine addiction, based on shared discriminative stimulus effects. However, subchronic DAT inhibitor treatments have so far failed to attenuate methamphetamine vs. food choice in monkeys (Banks and Blough, 2015; Schwienteck and Banks, 2015) or human laboratory methamphetamine self-administration (Stoops et al, 2015), and do not produce reliable and robust decreases in methamphetamine use in double blind, placebo-controlled clinical trials (Elkashef et al, 2008; Miles et al, 2013). Thus, the utility of ‘agonist-based’ DAT inhibitor medications for methamphetamine addiction remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%